دۆخ لە کرمانجیى ژووروودا - محەمەد, فەرەیدون عەبدول; قادر, عادل رشید (Sulaimani Journal for Humanities, 2002)
This work is devoted to recognizing the occurance of the gramatical case in Northern Kurdish. Northern Kurdish follows the Erestive system of langugaes, in which the object agrees with transitive verb in number and person in the past tens. In this analysis we conclude that: 1-Northern Kurdish hay for gramatical cases. 2-.1f the subject is not expressed by a personal pronoun in the past tense, thei case marker will be represented by the morpheme (ī) for masculine, and morepheme (Ē)for femeniane , and morepheme (an ) for plural, 3-1f the object is not expresed by a personal pronoun in the present tens, the case in markers will attach to the object.